Urinary human papillomavirus DNA as an indicator of gynaecological infection in young women in Schistosoma and HIV endemic South Africa - Pillay, P.; Galappaththi-Arachchige, H. N.; Taylor, M.; Roald, B.; Kjetland, E. F. (Frontiers in Global Women's Health, 2025)
BackgroundGlobally, Africa has the highest HIV, cervical cancer and schistosomiasis prevalence. Female Genital Schistosomiasis (FGS) is hypothesized to be associated with HIV and cervical atypia. Young women aged 15 and above, constituting almost 3 million of the South African population, have limited health care access and are at risk for this triad of diseases. Urinary HPV DNA analysis is a non-invasive sampling method that can assist in evaluating risk among this population. This study compared the analysis of HPV DNA in urine and cervico-vaginal lavage (CVL) samples to cytology Pap smear, Schistosoma microscopy and HIV results.MethodsIn this cross-sectional study, 235 young women aged 16 years and older from rural high schools in KwaZulu-Natal participated. HPV DNA analysis was done in urine and CVL samples. Pap smears were analysed for squamous cell atypia and urine microscopy was used for the identification of Schistosoma ova.ResultsUrinary schistosomiasis was reported in 49 (20.9%) and HIV detected in 49 (20.4%). Urinary and CVL HPV DNA was found in 147 (62.6%) and 177 (75.3%) respectively. Any atypia was detected cytologically among 173 (73.6%). The following associations were found using the Pearson Chi-Square and a Likelihood Ratio test: (a) between HIV positive status and urinary HPV DNA positive cases on both the urine (X2 = 5.007; p-value = 0.025) and (X2 = 4.264; p-value = 0.039) and between HIV positive status and CVL HPV DNA tests respectively (X2 = 5.165; p-value = 0.023) and (X2 = 4.321; p-value = 0.015), and (b) among urine HPV DNA and the CVL HPV DNA tests, where (X2 = 52.966; p-value = 0.001) and (X2 = 50.716; p-value = 0.001). Urine HPV DNA showed a sensitivity of 75.7% and specificity of 77.6% relative to the CVL HPV DNA. There was no statistical association between urinary schistosomiasis and HPV or with any atypia.ConclusionUrine has the potential of being optimized as an alternative and possibly more acceptable sample for HPV detection among young adolescent populations at risk in comparison to CVL samples. An integrated targeted intervention incorporating Schistosoma in addition to HPV and HIV testing needs consideration among young women in this age group from endemic areas.